Potret Kuota Perempuan di Parlemen - - Ratnawati (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2004)
In response to the slow progress in improving women role in politics, an affirmative action has been adopted in Indonesia. A scheme, which popularly known as